Development Analysis of Institutional Repository Website In the West Nusa Tenggara: Webometrics Study - Ridwan (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2023)
The global proliferation of institutional repositories has garnered significant attention, particularly from research-intensive institutions. This trend is crucial for effectively storing, disseminating, and providing access to copious research and scientific output, benefiting both the academic community and society. In Indonesia's research history, repositories have been extensively explored, with a focus on comprehensive research across the country's repositories. This study specifically analyzes institutional repositories in eight West Nusa Tenggara universities. Its objective is a quantitative depiction of higher education institutional repositories in West Nusa Tenggara, utilizing webometrics indicators. This descriptive quantitative research employs a webometrics study with data collected through observation and documentation. The analysis relies on webometrics indicators: Size (S), Visibility (V), Rich File (R), Scholar (Sc), and Weighting. The study showed that Mataram University's institutional repository secured the top webometrics ranking, excelling in Size (S), Visibility (V), and Scholar (Sc). Muhammadiyah University of Mataram follows, securing second place, while Mataram State Islamic University (UIN) claims third. Gunung Rinjani University's institutional repository in East Lombok ranks last among the eight repositories analyzed.